Herlyn-Werner-Wünderlich syndrome: case report - Andrés Felipe Figueroa-Blanco; Miguel Ángel Montañez-Aldana (Case Reports)
Introduction: The Herlyn-Werner-Wünderlich (HWW) syndrome is the association of three urogenital anatomic alterations of low incidence. Müllerian alterations are rare and are usually incidental findings; consequently, they are underdiagnosed and their genesis and correlation with having a higher probability of expression on the right side are unknown. Case Report: This is the case of a 17-year-old patient who consulted for severe hypogastric abdominal pain linked to foul-smelling bleeding. On physical examination, a vaginal septum was found, while complementary images showed uterus didelphys and renal agenesis, leading to diagnose HWW syndrome. Furthermore, pyometra and hematocolpus were also documented and managed with antibiotic therapy. Given the adequate response to treatment, hospital discharge was authorized with follow-up by external consultation, since the definitive management could not be provided during hospital stay. Discussion: One of the causes of recurrent abortions is the presence of this syndrome; however, when properly diagnosed, definitive treatment can be provided to reduce conceptional losses and urogenital hematopurulent collections. Conclusions: HWW syndrome is a rare malformation that increases the risk of suffering from gynecological infectious diseases or blood collections. Surgical management of the vaginal septum is a definitive treatment that improves quality of life and reduces the risk of morbidities associated with the pathology.